(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The aim of the current research is to prepare an integrated learning program based on mathematics standards for the next generation of the NYS and to investigate its impact on the development of the teaching performance of middle school mathematics teachers and the future thinking skills of their students. To achieve the objectives of the research, the researcher prepared a list of mathematics standards for the next generation, which were derived from a list of standards. He also prepared a list of the teaching competencies required for middle school mathematics teachers in light of the list of standards, as well as clarified the foundations of the training program and its objectives and the mathematical practices that include. Additionally, he prepared an electronic skill test for mathematics teachers and a test for future thinking skills for pupils on the stage. The research sample consisted of a group of mathematics teachers at the intermediate stage, numbering (40) teachers who were divided into two experimental and control groups, and a group of intermediate school students; whose number reached (60) students, were divided into two experimental and control groups as well. The results revealed that there are differences between the experimental and control groups of teachers in the post-measurement of the skill-test of the teaching performance in favor of the experimental group and in the pre-post-test measurements of the experimental group in favor of the post-measurement, The results showed also that there are differences between the experimental and control groups of students in the post-measurement to test future thinking skills in favor of the experimental group and differences in the pre-post measurements to test the future thinking skills of the experimental group of students in the intermediate stage in favor of the post-measurement. In light of these results, the researcher presented a set of recommendations for training and preparing mathematics teachers and also made some suggestions for future research similar to the current research.